Clove essential oil in the sanitation of fertile eggs - Oliveira, Gabriel da Silva (2020)
The aim of this study was to evaluate the efficacy of sanitizing fertile eggs with clove essential oil as an alternative to paraformaldehyde; effects on the reduction in eggshell microbial count, incubation yield, and neonatal chick quality were measured. A total of 1,460 brown fertile eggs with a mean weight of 58.64 ± 0.49 g (from 37-wk-old CPK [Pesadão Vermelho] breeder hens) were collected under aseptic conditions and randomly distributed into 4 treatments (nonsanitized and sanitized with grain alcohol, clove essential oil, and paraformaldehyde) before incubation. The count of total aerobic mesophilic bacteria was significantly lower after spraying with clove essential oil (2.30 ± 0.24 log10 CFU/mL) than on nonsanitized eggs (3.49 ± 0.34 log10 CFU/mL) or on eggs sprayed with grain alcohol (3.09 ± 0.14 log10 CFU/mL) but did not differ significantly from the count in the paraformaldehyde group (2.23 ± 0.29 log10 CFU/mL). The hatchability of fertile eggs differed significantly between the studied treatments. The mean values for the eggs treated with clove essential oil (84.69 ± 1.65%) and paraformaldehyde (81.87 ± 3.92%) were statistically similar but were higher than the negative control (74.03 ± 3.58%) and grain alcohol (73.59 ± 2.87%) values. In the Pasgar© score assessment, it was determined that the clove essential oil (9.21 ± 0.89%) had a superior effect on the physical quality of the chicks compared with the effects of the other treatments. Clove essential oil is effective and safe for eggs intended for incubation. Its use as an alternative to paraformaldehyde in the sanitation of fertile eggs is strongly recommended.